Molecular and functional characterization of endocannabinoid hydrolases - Mahmood, Nada (2018)
Background: It is now widely accepted that cannabinoids (whether synthetic or endogenous ligands) have multiple physiological, psychological and pathological effects. One area of research is investigating how to increase endogenous cannabinoid levels for potential therapeutic benefit, principally by pharmacological inhibition. However, many enzymes within the endocannabinoid system are lacking pharmacological tools such as inhibitors and/or defined substrate/s. Therefore, the development of high throughput screening assays for compound libraries will pave the way for investigation of the biochemical and pharmacological properties of these enzymes and will open the door for further in vivo studies.